Gangguan Stres Pascatrauma Dan Panggilan Penginjilan: Sebuah Refleksi Teologis dan Psikologis dari Kitab Yunus - Stimson Hutagalung (Jurnal Koinonia, 2021)
Evangelism is the Great Commission from God to mankind. God gave the same mandate to Jonah, but Jonah bravely refused the Great call. This study tries to find out why Jonah was "too brave" to reject God's great call and go to Tarshish? And why then did he change course from Tarshish to Nineveh? This study used a qualitative method with a descriptive analysis approach through a literature review of the biblical text. In conclusion, Jonah's "too brave" action in rejecting God's Great call was caused by the post-traumatic stress disorder he experienced with his family from childhood to adulthood during the Syrian invasion of Northern Israel, resulting in his intense antagonism towards Nineveh which made him drift away from God. When Jonah's post-traumatic stress disorder was treated with complete surrender through prayer, Jonah was given the courage, fortitude, and determination to spread the news of salvation to the city of Nineveh.